(untitled) (Research, Society and Development, 2020)
This article aims to identify the bases that support and give meaning to the Institutional Scientific Initiation Scholarship Program (PIBIC), promoted by the Research Support Foundation of the State of Bahia (FAPESB), in addition to trying to evaluate what its results have been. The research is justified not only by the scarcity of studies that discuss the effectiveness of similar programs in Brazil, but, above all, by the fact that FAPESB has started to support it more and more intensely in recent years. Regarding the data that supported the analyzes carried out, they were obtained through documentary research, structured based on the analysis of the IC scholarship holder records, provided by the supported Universities, since the creation of the Program in 2003, until the year 2010. The described scenario showed, in general terms, that the PIBIC / FAPESB contributed not only quantitatively, but also qualitatively to the formation of human capital in Bahia, with its reflexes being felt more intensely in the institutions that integrated it.